Features of Formation Developing Educational Environment in the Conditions of Standardization of Primary Education of Ukraine - Smoliyk, Svitlana (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
In the article on the basis of the scientific literature study, the peculiarities of the formation of the educational environment in the modern elementary school are highlighted. The basic components (informational, social-psychological, cultural-educational and material-technical) as well as components of innovative educational environment of elementary school (spatial, informative, communicative) are substantiated. In the structure of the educational environment of the school, the author identifies the following functions: didactic-educational, information-developing, coordinative, adaptive-emotional, socio-cultural, communicative, integrative, which ensure the integrity and systemic functioning of the simulated environment of the elementary school. The basic aspects of psychological and pedagogical expertise of the developing educational environment are determined in the paper. The stages of activity of all the subjects of educational-educational interaction (students, teachers, parents) in the subject-content functioning of the developing educational environment of primary school are singled out